Stadsplaneringsideal. Med den periurbana zonen i fokus - dess potential för den hållbara staden - Hansson Broman, moa (SLU/Landscape Architecture (until 121231), 2010)
To be able to plan for the expansion of a town, one needs a vision of the future appear-ance of the town. It is the current issues (social situation, supply and demand, political control etc.) which decide what the ideal for town planning is. This is turn is the steering factor of the physical structure of the town. Therefore, the town's structure is decided by these ideals. In this report, I will present planning ideals that have historically been, and which criticisms that have been directed towards them. With reference to these issues, I will present those guidelines and ideals we have today for planning of our towns. Urbanisa-tion during the period of industrialization led to sanitary problems in towns. From these problems, a dream was born to escape from the town's tight, cramped and miserable conditions. The result of this dream became the "town garden" ideal. The vision was to live in a location, where one could have the conveniences of the town, but with the natu-ral freshness of the countryside: a house with its own garden. These first housing sub-urbs were placed in the periurban zone, on agricultural land on the boundaries of the town. Up until now, one can see that this concept still holds and is strong. The develop-ment of lawns continues to flourish in the zone that borders town and countryside. It is therefore the case that towns are expanding in the periurban zones with both house-building and with large space-consuming/demanding non-domestic buildings. Issues in town planning become clear in the periurban zone as conflicts of interest are prevalent. Agriculture, housing, industry and shopping centers compete for space in this zone, at the cost of the potential near-urban recreation, which also can be found in the periurban zone. To relate the report and town-planning issues to a place in Sweden, I have chosen to look at the borough of Lund and its presentation material for the over-view plan 2010 (2009). More specifically, in the suburb of "Brunnshög". Brunnshög is an area in the periurban zone. Although the borough of Lund has a strong ideal of "a dense city" the town and conserves agricultural land, which surrounds Lund, it plans to build large-scale non-domestic constructions in just this zone. The periurban zone carries a complexity, which makes the area difficult to plan and define. Its multifunctionality may be seen as a hinder for the physical planning, but should be taken as a possibility. The "compact" ideal of today may be interpreted as a counterreaction to the long-running trend, that lawns and large-scale non-domestic buildings, until now, have expanded into the boundaries between town and countryside.